Capital allocation in decentralized businesses - Stuart M. Turnbull (Journal of Risk and Financial Management, 2018)
This paper described a theory of capital allocation for decentralized businesses, taking into account the costs associated with risk capital. We derive an adjusted present value expression for making investment decisions, that incorporates the time varying profile of risk capital. We discuss the implications for business performance measurement.
Keywords: 330; risk capital; capital allocation; decentralization; performance measurement; RAROC